Program Pemberdayaan Pengaruhnya terhadap Pertumbuhan Usaha Kecil di Propinsi Riau - Zulkarnain, Zulkarnain (Universitas Brawijaya, Indonesia, 2008)
In the effort to developing their businesses, small business should have owned entrepreneurial characteristics and entrepreneurial behavior, also business motivation and competencies. Eventhough the empowerment program has been issued by the government, it has not yet given an optimal contribution to the entrepreneurial characteristics and business growth. The purpose of this research is; Firstly, to clarify the correlation among the variables empowerment program, entrepreneurial characteristic, business motivation, entrepreneurial behavior, business competency, small business growth. Secondly, to give recomendation and create an optimum model for relation among variable empowerment program to small business in line with their real needs are required. Some important findings of the research are as follow; Firstly, the empowerment program carried out directly has not develop the compentencies and growth of business. Secondly, the strong of empowerment program ditermineded by the government financial resources. Thirdly, entrepreneurial characteristics ditermine by creativity and innovation indicators to increase the motivation and business growth. Fourthly, the strong motivation ditermine by growth of vision indicators which can increase business growth. Fiftly; the strong entrepreneurial behavior ditermine by entreprenership cultures indicators which can increase business competence through business motivation. Sixthly; the strong business competencies ditermine by the leadership competence indikator. Seventhly; the empowerment program carried out by the government through entrepreneruship cultures development and high growth of vision will increase business growth.